The influence of weapons development throughout history and the protection of the civilian population: Issues of application of international conventions - Lopičić-Jančić Jelena Đ.; Vasić Ljubica M. (Srpska Politička Misao)
Numerous wars and armed conflicts have been waged for the last hundred years worldwide. They have resulted in the deaths and injuries of the civilian population, as well as the destruction of cities, villages, settlements, economic facilities and other infrastructure. Unfortunately, wars and armed conflicts continue in various parts of the world, and more and more people are killed which are primarily civilian population. It is necessary that the role of the international community in general, as well as the largest international organizations like OUN, should have more active roles in the terms of the application of all legal frameworks worldwide. That is related to the control of weapons in general and weapons of mass destruction and therefore the protection of all persons protected according to the Geneva Conventions from 1949. Those are primarily the civilian population, wounded, sick, prisoners of war, shipwrecked as well as property, etc. From a global perspective, the international community needs to be more active to try on diplomatic and political level to minimize as much as possible occurrence of war, arm conflict and any kind of armed crisis. In that way the idea of usage of weapons in general and weapon for mass destructions will not be current and civilian population will be more protected.